(untitled) (Annual of the Faculty of Philosophy in Skopje, 2011)
Christianity in Ohrid has been present for a long time and throughout history it has appeared in various forms and with different intensity. The missionary work of St. Erazmus of Lychnidos (late 3rd century); the existence of the Lychnidos Bishopric (the 4th- end of the 6th century); then a kind of a renewal of the late antique church presented by the Byzantine Ohrid Bishopric (9th century) and certain parallel Slav missionary-educational work of St. Clement of Ohrid; and finally the foundation of the Ohrid Archbishopric/Patriarchate (11th-18th century), which with its high church status and many years of being active left the most lasting mark on the development of the Christian institutional organising in the town of Ohrid and wider in Macedonia. However, it seems that in science the appearance and the activity of the Ohrid Bishopric in the 9th century has been rather neglected and has not received the proper treatment, to the advantage of the more comprehensive presence of issues related to St. Clement and the Ohrid Archbishopric. In regard to this Byzantium institution as especially important for the scientific elaboration are the following issues: the time and the military- political context for the emergence of the Bishopric; the supposed consequences from the Bulgarian conquering of Ohrid; the probable temporary Romaioi-Slav parallelism in the church affairs in Ohrid; the possible reasons and circumstances for the abolition or pushing out of the Bishopric, etc. In this scientific contribution we try to offer partial or complete answers to the posed questions being aware of their utter complexity.